METODOLOGI TAFSIR PADA AWAL PERKEMBANGAN ISLAM - Manaf, Abdul; Hidayati, Hidayati (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2022)
Interpretation activities has beginning in the time of the prophet Muhammad Saw, sahabat, and tabiin, even today. However, not many people know the forms and methods of interpretation that existed at the beginning of the development of Islam, both interpretations at the time of the Prophet, sahabat, and tabiin. This study aims to determine the methodology of interpretation in the early days of Islam, by studying and analyzing the steps of interpretation from each time. As the first interpreter, the Prophet Muhammad began his interpretation by referring to the Qur'an. It is not uncommon for the existence of the meaning of one verse to be explained by another verse. If this is not the case then the Prophet Muhammad pbuh will determine based on the sunah. The Prophet's determination with regard to the Qur'an was the result of his understanding of revelation. The method of interpretation carried out by friends begins with exploring the interpretation of the Qur'an itself, then based on the sunah of the Prophet Muhammad Saw, berijtihad to find new understanding, and finally the master of the book. The interpretation activities carried out by friends were then followed by the tabiin generation. The tabiin method of interpretation is almost the same as the method of sahabat interpretation. By knowing the methodology of interpretation it can be understood that the activity of interpretation cannot be carried out by just anyone without following the rules and ethics of interpretation. As a result, the resulting interpretation will be false and misleading.